2013
DOI: 10.3944/aott.2013.3015
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of Ethibond sutures and semitendinosus autograft in the surgical treatment of acromioclavicular dislocation

Abstract: Since both surgical techniques led to satisfactory results, reduction of ACJ, excellent functional score and acceptable patient satisfaction, No. 5 Ethibond suture technique could be recommended as the treatment of choice due to the absence of morbidity in removing semitendinosus autograft tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Several other authors have found similar results after ACCR with tendon grafts. [32][33][34][35][36][37][38][39][40] In our study the mean ASES score improved from 58.9 preoperatively to 93.8 postoperatively, with a high median patient satisfaction rating of 9 of 10.…”
Section: Discussionmentioning
confidence: 62%
“…Several other authors have found similar results after ACCR with tendon grafts. [32][33][34][35][36][37][38][39][40] In our study the mean ASES score improved from 58.9 preoperatively to 93.8 postoperatively, with a high median patient satisfaction rating of 9 of 10.…”
Section: Discussionmentioning
confidence: 62%
“…The disadvantages of surgery are the requirement for anaesthesia, the risk of infection and the possibility of degenerative arthritis [7, 20]. Superficial wound site infection following AC joint luxation has been reported in literature at rates of 0%–53% [13]. In our study, we carried out surgery for all Type III dislocations and observed one superficial infection whom healing by antibiotherapy.…”
Section: Discussionmentioning
confidence: 69%
“…As one of the most important joints around the shoulder, injuries to the acromioclavicular joint (AC) are very important, as depending on the degree of injury, they cause restrictions to the daily life of the patient and workforce losses. Although several treatment methods have been described in literature, it has not been fully clarified which type of treatment is recommended for which type of dislocation [16]. The degree of injury and the functional expectations of the patient are the primary indicators.…”
mentioning
confidence: 99%
“…Male / Female 5: 1 (1)(2). Although conservative and surgical treatment options have been defined in the treatment of Type III AC joint dislocations, it has not been clarified which method is better (3,4). Dias JJ et al reported that conservative treatment was better than surgical treatment (5).…”
Section: Introductionmentioning
confidence: 99%